Do cognitive tasks during gait increase the risk of accidents with pedestrians? A study based on electromyographic parameters - Hallal, Camilla Zamfolini; Navega, Marcelo Tavella; Silva, José Adolfo Menezes Garcia; Spinoso, Deborah Hebling; Morcelli, Mary Hellen; Crozara, Luciano Fernandes; Marques, Nise Ribeiro (Pontifícia Universidade Católica do Paraná, 2017)
AbstractIntroduction Accidents involving pedestrians are responsible for many cases of serious injuries and deaths. Crossing streets safely requires complex planning and cognitive demand because it is necessary to perform more than one task at a time.Objective The aim of this study was to identify electromyographic changes during gait in young subjects who performed the cognitive tasks concurrently.Methods The study included 17 younger women aged between 18 and 25 years. Data collection was performed on a treadmill. The volunteers were instructed to walk in four different conditions: normal gait (NG), gait with dual easy task (DET), gait with dual hard task (DHT) and gait with dual mixed task (DMT).Results Significant differences were found between the MN condition to the other conditions for all muscles and, during the NG, smaller values of muscle activation were found. Muscle co-contraction between muscles VM / BF showed a significant difference between the conditions of NG and DMT (p = 0.04) and, during the NG, smaller values of co-contraction were observed.Conclusion The data of this study permits to conclude that the competition between motor and cognitive resources significantly affects the levels of muscle activation and co-contraction during gait in young adult women. Thus, we conclude that the performance of dual cognitive tasks while driving can be considered a risk factor for safe driving.

ResumoIntrodução Os acidentes de trânsito envolvendo pedestres são responsáveis por muitos casos de lesões graves e óbitos. Atravessar a rua com segurança requer complexo planejamento e demanda cognitiva, pois é necessário realizar mais de uma tarefa ao mesmo tempo.Objetivo O objetivo do presente estudo foi identificar alterações eletromiográficas durante a marcha de indivíduos jovens realizada concomitantemente com tarefas cognitivas.Métodos Participaram do estudo 17 jovens do sexo feminino com idade entre 18 e 25 anos. A coleta de dados foi realizada em esteira ergométrica onde os voluntários realizaram o teste de marcha compostos por quatro condições distintas: marcha normal (MN), marcha com dupla tarefa fácil (DTF), marcha com dupla tarefa difícil (DTD) e marcha com dupla tarefa mista (DTM).Resultados Foram encontradas diferenças significativas entre a condição de MN para as demais condições para todos os músculos, sendo que durante a MN foram encontrados menores valores de ativação muscular. A co-contração muscular entre os músculos VM/BF mostrou diferença significativa entre as condições de MN e DTM (p = 0,04), sendo que durante a MN foram observados menores valores de co-contração.Conclusão Os dados do presente estudo, nos permitem concluir que a competição entre recursos motores e cognitivos afeta, significantemente, os níveis de ativação muscular e co-contração durante a marcha de mulheres adultas jovens. Assim, concluímos que a realização de duplas tarefas cognitivas durante a marcha pode ser considerada um fator de risco para o desempenho seguro da mesma, podendo ocasionar maior risco de acidentes aos pedestres.
Tarefas cognitivas durante a marcha aumentam o risco de acidentes com pedestres? Um estudo baseado em parâmetros eletromiográficos
Keywords: Gait; Falls; Electromyography; Marcha; Quedas; Eletromiografia